Challenges and Paradigms in Applied Robust Control 2011
DOI: 10.5772/19316
|View full text |Cite
|
Sign up to set email alerts
|

Robust Multivariable Control of Ill-Conditioned Plants – A Case Study for High-Purity Distillation

Abstract: The main objective of this book is to present important challenges and paradigms in the field of applied robust control design and implementation. Book contains a broad range of well worked out, recent application studies which include but are not limited to H-infinity, sliding mode, robust PID and fault tolerant based control systems. The contributions enrich the current state of the art, and encourage new applications of robust control techniques in various engineering and non-engineering systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Although there are many studies on the control of distillation columns, they focus only on columns of low to moderate purity. Multivariable control with a single-input, single-output (SISO) control structure was typically applied. Such control techniques may not be applicable for a high-purity distillation column that exhibits ill conditioning. Thus, an effective control strategy that provides strong robustness so as to achieve the desired high-purity product is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are many studies on the control of distillation columns, they focus only on columns of low to moderate purity. Multivariable control with a single-input, single-output (SISO) control structure was typically applied. Such control techniques may not be applicable for a high-purity distillation column that exhibits ill conditioning. Thus, an effective control strategy that provides strong robustness so as to achieve the desired high-purity product is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic and steady-state indicators are used in different articles. Some authors have used steady-state indices; others have preferred frequency-dependent indices …”
Section: Introductionmentioning
confidence: 99%
“…Semino et al designed a double-filter internal model control (IMC) controller for ill-conditioned distillation columns. Razzaghi and Shahraki , showed that acceptable closed-loop performance could be achieved for an ill-conditioned high-purity distillation column by use of the structured singular value. The benefit of this method is its reliance on a simple filter structure depending on fewer parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Since the order of the ODOF controller is usually high, TDOF controllers are designed for the CDC benchmark problem in refs . Yaniv et al proposed a quantitative feedback theory (QFT) approach for the ill-conditioned plant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation